Peningkatan Pengetahuan Masyarakat Dusun Tawang Desa Mendiro melalui Edukasi Pemahaman Label Pangan: Peningkatan Pengetahuan Masyarakat Dusun Tawang Desa Mendiro melalui Edukasi Pemahaman Label Pangan - Atira Firdausi; Sri Hany Kusuma Marpaung Muladi; Indahtul Mufidah (PC IAI Sragen, 2026)
The public's lack of understanding regarding food labeling poses serious health risks due to the consumption of unsafe products or those that do not meet nutritional requirements. This community service initiative aimed to enhance the knowledge of residents in Tawang Hamlet, Mendiro Village, concerning food label literacy and the critical interpretation of nutritional information. The methodology employed was interactive educational lectures and practical simulations, integrated into routine community religious gatherings. Evaluation results indicated a marked improvement in public knowledge regarding food label comprehension following the program, with participants demonstrating the ability to identify key information such as expiration dates, distribution permits, and nutritional compositions on product packaging. This education must not remain a one-time program; rather, it should evolve into a sustainable movement that positions housewives as primary decision-makers. The resulting shift in consumption behavior will have a systemic impact on elevating family food safety standards and ensuring long-term health protection.